Urbanization and Sustainable Cities in Nigeria - Ebikabowei Aduku; Ifeoma Eboh; Chibuzo Egbuchulam (Yayasan Riset dan Pengembangan Intelektual, 2021)
Rapid urbanization is on the increase especially in the developing countries and, the need for shaping sustainable cities continues to draw widespread recognition and has remained a major concern. Thus, urbanization and sustainable cities in Nigeria is examined using descriptive technique and came up with several lessons. Arable land is declining following fast increasing urban population growth. Arable land may not be capable of sustaining to meet the needs of the future generation, as the urban population continues to increase except appropriate policies are put in place to control it. Nitrous oxide emissions also rise at a faster rate, rising above the urban population growth. Such a trend means jeopardizing sustainable cities. Renewable energy consumption is falling while CO2 emissions are rising, which undermines sustainable city. Urbanization is fast increasing and cities are formed but the cities are not sustainable. We recommend infrastructural development in Peri-urban areas and rural areas. This will facilitate the urbanization process and city borders can be expanded and spread out to absorb neighbouring cities. In this way, urban population agglomerations will reduce and more arable land will be available. Also, the efficient use of renewable energy systems is recommended.